2019
DOI: 10.1002/mc.23111
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin receptor 1 is a new therapeutic target for human undifferentiated pleomorphic sarcoma growth

Abstract: Undifferentiated pleomorphic sarcoma (UPS) is the second most common soft tissue sarcoma. For patients with unresectable or metastatic disease, chemotherapies are considered, but in many cases they are not curative. There is a need to identify specific molecular dysregulations that can be therapeutic targets. We focused on neurotensin receptor 1 (NTSR1), which belongs to the G‐protein‐coupled receptor. NTSR1 expression was upregulated in specimens from patients with UPS. Real‐time polymerase chain reaction sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Neurotensin receptor 1 (NTSR1) was a component of GPCR, and its knockdown significantly prevented the aggressive behavior of UPS cells. SR48692, an inhibitor of NTSR1, was found to synergistically coordinate with chemotherapeutic agents to prevent UPS cell proliferation by inactivating extracellular kinase ( Tokumoto et al, 2019 ). NTSR1 might be another target for UPS treatment.…”
Section: Targeting Therapymentioning
confidence: 99%
“…Neurotensin receptor 1 (NTSR1) was a component of GPCR, and its knockdown significantly prevented the aggressive behavior of UPS cells. SR48692, an inhibitor of NTSR1, was found to synergistically coordinate with chemotherapeutic agents to prevent UPS cell proliferation by inactivating extracellular kinase ( Tokumoto et al, 2019 ). NTSR1 might be another target for UPS treatment.…”
Section: Targeting Therapymentioning
confidence: 99%
“…Christina L. Roland found that cyclin D1, pEGFR, pIGF-1R, and PTEN deletion ( p < 0.001) and AXL overexpression ( p = 0.015) were associated with reduced disease-specific survival (DSS) ( 58 ). In addition, neurotensin receptor 1 (NTSR1) ( 59 ), anti-human tumor endothelin 1 (TEM-1) ( 60 ), and various other targeted therapeutic targets are under progressive research by related scholars and may become effective for the treatment of this disease in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Research into the cell signaling pathways and cell cycle regulation in UPS has paved the way for the use of phosphoinositide 3-kinase (PI3K) inhibitors, which, when combined with agents like doxorubicin, have significantly delayed tumor growth [87]. The exploration of other targets, such as Neurotensin Receptor 1 (NTSR1) and Fibroblast Growth Factor 23 (FGF23), continues to provide new insights into potential therapeutic strategies that could impede the aggressive behavior and proliferation of UPS cells [29,88].…”
Section: Targeted Therapy In the Management Of Undifferentiated Pleom...mentioning
confidence: 99%